Kecerdasan Pelbagai dan Minat Kerjaya dalam Kalangan Pelajar Sekolah Menengah - Muzarina Juhari; Ku Suhaila Ku Johari; MohdIzwan Mahmud (RedwhitePress)
Intelligence is the ability to learn, understand, reason and solve problems effectively and the ability to contribute positively to the societies. This study was conducted to identify the multiple intelligence stage and career interest patterns among 77 secondary school students. This study is a quantitative that represents descriptive data analysis. The Inventory of Multiple Intelligence and Inventory of Career Interest were analyze using Statistical Package for Social Science (SPSS). The result of the study shows that the level of intelligence of form 3 students is moderate. A total of nine intelligence domains, verbal/visual linguistic is at moderate level of 54.2%, Naturalistic 51.8%, Visual Spatial domain is at 49.4%, Kinesthetic and Intrapersonal both at 47%, followed by Mathematic at 41%, Music and Interpersonal each at 34.9%. Existential domain is the lowest percentage in the study at 27.7%. This study suggests to examine the correlation of multiple intelligence and career interest toward academic achievement among students.